Cs2Bi2O(Ge2O7) (CBGO): A Larger SHG Effect Induced by Synergistic Polarizations of BiO5 Polyhedra and GeO4 Tetrahedra - Tang, Ru‐Ling; Hu, Chun‐Li; Wu, Bao‐Lin; Fang, Zhi; Chen, Yan; Mao, Jiang‐Gao (Angewandte Chemie International Edition, 2019)
A cesium bismuth germanate, Cs2Bi2O(Ge2O7) (CBGO), was synthesized by a traditional high‐temperature solid‐state reaction. Its structure features a 3D network composed of a 1D chains composed of Bi2O8 dimers that are further bridged by Ge2O7 dimers, forming tunnels of seven member rings (MRs) that are filled by the Cs+ cations. CBGO exhibits extraordinary larger second harmonic generation (SHG) response of about 13.7 times that of KDP (KH2PO4) under 1064 nm laser radiation and 1.1 times that of KTP (KTiOPO4) under 2.05 μm laser radiation, which is the highest among all of the metal germanates reported so far. CBGO possesses a moderate birefringence (0.073 at 1064 nm) and is phase matchable. Furthermore, CBGO melts congruently and exhibits high thermal stability. The metal germanate, CBGO, has been prepared through the introduction of Bi3+ and Cs+ into germanate. It features a 3D network composed of a 1D chains composed of Bi2O8 dimers that are further bridged by Ge2O7 dimers, that confines the BiO5 and GeO4 units to be assembled in a favorable alignment fashion and displays quite a large SHG efficiency of about 13.7 times that of KDP.